Поставь вместо * знак + или знак - так чтобы получилось верное равенство: а) - a + b - c + d + k - m - n + j + f - z = - ( * a * b * c ) - ( * d * k ) + ( * m * n * j ) + ( * f * z ) б) *a *b *c *d * k *m *n* j* f *z = - (-a + b - c )+ (- d + k - m ) - (+ n - j -f + z )

nemcevakata401 nemcevakata401    3   31.05.2019 00:30    1

Ответы
polyaХеХеХе polyaХеХеХе  01.07.2020 10:04
A) -a+b-c+d+k-m-n+j+f-z=-(+a-b+c)-(-d-k)+(-m-n+j)+(+f-z)
б) +a-b+c-d+k-m-n+j+f-z=-(-a+b-c)+(-d+k-m)-(+n-j-f+z)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика